The association between waist-to-height index and prostate cancer risk: evidence from the NHANES study - Gao, Qinghe; Lin, Zongqi; Zhang, Yihua; Cai, Jiantong; Li, Shaopeng (Frontiers in Nutrition, 2025)
BackgroundProstate cancer (PCa) is associated with obesity, especially visceral fat. WWI may reflect the distribution of body fat more accurately. However, it is unclear whether WWI is associated with the risk of developing PCa.MethodsSeventy thousand one hundred and ninety participants took part in the National Health and Nutrition Examination Survey (NHANES). The associations between WWI and PCa risk were analyzed through multiple regression. The association between WWI and prostate cancer was analyzed in subgroups using stratified factors, with interaction tests performed to evaluate the stability of this association across subgroups. In addition, restricted cubic sample plots and threshold effects were examined to further explore the nonlinear association between WWI and prostate cancer. Finally, subject work characteristics (ROC) curves were used to evaluate the accuracy of different obesity indicators in predicting PCa.ResultsMultiple regression analyses revealed that those individuals with a higher WWI index had a higher prevalence of prostate cancer, while subgroup analyses and interaction tests showed that the correlation between WWI and the prevalence of PCa differed across age groups (interaction p < 0.05). The ROC curves showed that the predictive power of WWI for the prevalence of PCa was superior to that of traditional indicators of obesity (both p < 0.05).ConclusionThere was a positive and significant association between PCa risk and WWI, especially in male participants aged <60 years. Further comprehensive studies are required to confirm our findings.